Five New Hypocrealean Species from Algae and Sediment in the Intertidal Zones of China - Meng-Meng Wang; Wang-Ying Mo; Meng-Yi Sun; Ye-Hui Tu; Wei Li (Journal of Fungi)
Hypocrealean fungi are a well-documented group of fungi, with a wide range of ecological roles that include saprobic, parasitic, and endophytic forms, capable of thriving in diverse environments, both terrestrial and marine. Members in this group are abundant and widely distributed in marine environments around the world. However, the species diversity and distribution of this fungal group in Chinese seas is rarely reported. This study introduces five new species, namely Fusarium flavoides M.M. Wang & W. Li, Gliomastix fasciculata M.M. Wang & W. Li, Marquandomyces ulvae M.M. Wang & W. Li, Stephanonectria arenicola M.M. Wang & W. Li, and Verruciconidia oligospora M.M. Wang & W. Li, based on morphological characteristics and LSU-ITS-tef1-rpb2 phylogenetics. These new species were discovered from marine algae (Ulva spinulosa) and sediments (mud and sand). A detailed comparison of these new species and their close relatives is also presented.